MARTIN LUTHER KING JR’S PHILOSOPHY OF NON-VIOLENCE: A PARADIGM FOR GLOBAL BLACK RACE TOWARDS CONFLICT RESOLUTION AND PEACE IN AFRICA - Onoh John Ulafor (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2020)
The black race has suffered indignation across the globe through the machinations of oppressive, discriminatory and racist tendencies of developed nations. In United States and Europe, the black man in history had been consistently dehumanized and faced by social injustice. In this article I intend to articulate and examine the possible ways of how the black race could resolve conflicts and attain peace in Africa and across the globe. This would be done through the paradigm of non-violence philosophy of Martin Luther King Jr. Cognizance is accorded to the fact that, the non-violence paradigm had been successfully utilized by Martin Luther King Jr. in the United States to conquer racial discrimination and social injustice. I conclude in this paper that the reliance and efficacy of non-violence in conflict resolution and peace in Africa is a possibility.